The Effects of Alcoholic Extract of Ficus carica Leaves on Some Chemical and Microbiological Properties of Beef during Refrigerated Storage - Haider, Naeam; Rafi, Zahraa; Hussein, Rowaida Abdel; Emad, Batoul (Iraqi Journal of Science, 2023)
This study explored the preservative effects of the alcoholic leaves’ extract of Ficus carica plant on beef refrigerated for 15 days. Phytochemical analysis showed that the plant extract contained terpenoids, flavonoids, tannins, saponins, and alkaloids. Furthermore, the alcoholic extract of plants significantly reduced the total viable counts of psychrotrophic bacteria, pathogenic bacteria (Proteus, Salmonella typhimiurum, Escherichia coli, and Staphylococcus aureus), and yeasts (Candida kruse, Candida lambica, and Zygosaccharomyces) isolated from meat samples, particularly at 100 and 200 mg/ml concentrations.The antioxidant activity of the extract was determined by using TBA and TVN values. The results showed that meat samples treated with 100 and 200 mg/ml of the alcoholic extract of F. carica had significantly lower TBA values (25, 0.24 mg/kg respectively) on day 5 which became 0.92, 0.53 mg/kg on day 15. Whereas the control values increased from 0.25 to 1.75 mg/kg on day 15,f ollowed by the TVN values of treatment meat samples with 100 and 200 mg/ml 5.57, 5.12 mg N/100 g meat respectively on day 5 which became 12.16, 10.65 mg N/ 100 g meat on day 15, while the TVN in control samples increased significantly (p < 0.05) from 7.35 to 15.76 mg N/100 g meat.All results confirmed that the alcoholic extract of F. carica, which is rich in bioactive compounds is more effective as a natural antibacterial, antifungal and antioxidant, than synthetic antioxidants that maintain the quality of beef, compared to the control by reducing lipid oxidation and microbial growth at refrigeration temperatures, especially at 100 and 200 mg/ml concentrations of the plant extract.